Quorum Sensing and Spoilage Potential of Psychrotrophic Enterobacteriaceae Isolated from Milk. (22nd October 2018) - Martins, Maurilio Lopes; Pinto, Uelinton Manoel; Riedel, Katharina; Vanetti, Maria Cristina Dantas
Abstract : The 16S rDNA of six psychrotrophic Enterobacteriaceae isolated from cold raw milk were sequenced and the isolate 039 was identified as Pantoea sp., isolates 059, 068, and 071 were identified as Hafnia alvei, 067 was identified as Enterobacter sp., and 099 was identified as Aeromonas hydrophila . They presented different spoilage potentials in milk with A. hydrophila 099 being the most deteriorative. Only Pantoea sp. 039 was not able to induce the quorum sensing monitor strains of acyl homoserine lactones (AHLs). The halI gene, which encodes the AHL synthase in H. alvei, was identified in the isolates 059, 067, 068, and 071. After initial sequencing characterization and cloning, this gene showed its function by the heterologous synthesis of N-hexanoyl-DL-homoserine lactone and N-3-oxohexanoyl-L-homoserine lactone in Escherichia coli . In addition to producing AHLs, A. hydrophila 099 produced AI-2 in higher level than the assay's positive control Vibrio harveyi BB120. Therefore, Enterobacteriaceae strains isolated from cooled raw milk produce a rich array of signaling molecules that may influence bacterial traits in the milk environment.